MALIGNANT PERIPHERAL NERVE SHEATH TUMORS SPINE METASTASES - DOCUMENT REVIEW A CASE REPORTS (Vietnam Journal of Community Medicine, 2022)
Malignant Peripheral Nerve Sheath Tumors (MPNSTs) are rare, high-grade soft tissue sarcomasof extranodal origin and often metastasize early. The World Health Organization has coined theterm MPNST to replace previously heterogeneous and often confusing terms, such as malignantschwannoma, malignant neurilemmoma, neurogenic sarcoma and neurofibrosarcoma. MPNSTsarise from the sheaths of peripheral nerve fibers, either from Schwann cells or from neural crestderived pluripotent cells. Schwann cells are believed to be responsible for the formation of benign aswell as malignant tumors in the nerve fiber sheath. MPNST can appear in many places in the body,but in the lungs is extremely rare. Imaging is usually nonspecific. The diagnosis was confirmedby immunohistochemistry. We report a case of MPNST in the lung, with spinal metastases; wasconfirmed by biopsy of metastatic lesions and immunohistochemistry at the National Lung Hospital.
Keywords: Malignant Peripheral Nerve Sheath Tumor, malignant neurilemmoma, malignants chwannoma, neurofibrosarcoma.